1993
DOI: 10.1177/154193129303701811
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Correlating Visual Scene Elements with Simulator Sickness Incidence

Abstract: Simulator sickness occurs in a large number of Army, Navy, and Marine Corps simulators, and is most prevalent in moving-base, rotary-wing devices which employ cathode ray tube (CRT) video displays as opposed to fixed-wing, dome-display trainers with no motion base. Based on data from a factor analysis of over 1000 Navy and Marine Corps pilot simulation exposures, a new scoring procedure was applied to two helicopter simulators with similar rates of simulator sickness incidence. Based on the factor analytic sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The spatial frequency inside an optokinetic drum can easily be calculated because of its regular pattern, but it is more difficult to measure the average spatial frequencies of a VE. Kennedy, Berbaum, and Smith (1993), Kennedy, Drexler, and Berbaum (1994), and Kennedy, Berbaum, Dunlap, and Hettinger (1996) developed the first automated method to quantify the visual stimulus for the study of cybersickness. The reported method was referred to as the "human judged kinematics cluster score" (Kennedy, Berbaum, et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The spatial frequency inside an optokinetic drum can easily be calculated because of its regular pattern, but it is more difficult to measure the average spatial frequencies of a VE. Kennedy, Berbaum, and Smith (1993), Kennedy, Drexler, and Berbaum (1994), and Kennedy, Berbaum, Dunlap, and Hettinger (1996) developed the first automated method to quantify the visual stimulus for the study of cybersickness. The reported method was referred to as the "human judged kinematics cluster score" (Kennedy, Berbaum, et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…There are several available approaches to measuring cognitive performance (Dinges, 1992;Kennedy, Berbaum, & Smith, 1993;Kennedy, Dunlap, Turnage, & Wdkes, 1993), most of which have been incorporated into several different computer software packages. The program chosen for this study was E-Prime (Psychology Software Tools, Beta Version 1.0, November 19991, ~rimarily because this software program allows customizing the test design.…”
Section: Cognitive Performance Taskmentioning
confidence: 99%
“…An investigation in flight simulators showed that simulator sickness occurs far more rarely when the visual display is improved, without the motion simulation being changed (Kennedy et al, 1993). not caused by technology.…”
Section: Advantages and Limits Of Simulatorsmentioning
confidence: 99%